Characterization of three Lactobacillus delbrueckii subsp. bulgaricus phages and the physicochemical analysis of phage adsorption - Quiberoni, Andrea del Lujan (2004)
Aims: Three indigenous Lactobacillus delbrueckii subsp. bulgaricus bacteriophages and their adsorption process were characterized. Methods and Results: Phages belonged to Bradley's group B or the Siphoviridae family (morphotype B1). They showed low burst size and short latent periods. A remarkably high sensitivity to pH was also demonstrated. Indigenous phage genomes were linear and double-stranded DNA molecules of approx. 31-34 kbp, with distinctive restriction patterns. Only one phage genome appeared to contain cohesive ends. Calcium ions did not influence phage adsorption, but it was necessary to accelerate cell lysis and improve plaque formation. The adsorption kinetics were similar on viable and nonviable cells, and the adsorption rates were high between 0 and 50°C. SDS and proteinase K treatments did not influence the phage adsorption but mutanolysin and TCA reduced it appreciably. No significant inhibitory effect on phage adsorption was observed for the saccharides tested. This study also revealed the irreversibility of phage adsorption to their hosts. Conclusions, Significance and Impact of the Study: The study increases the knowledge on phages of thermophilic lactic acid bacteria.